Silicone rubber composition and method for producing same
By combining a silicone rubber composition with a specific composition, including high molecular weight organopolysiloxane and enhanced silica and sodium polyacrylate, the problem of poor sliding properties of the silicone rubber surface when wet is solved, and the effect of low friction coefficient during wet and good mechanical properties is achieved when drying is achieved.
Patent Information
- Application Number
- JP2021209350
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-23
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-12-23
AI Technical Summary
The prior art is difficult to achieve excellent sliding properties of the silicone rubber surface when wet and disappear when drying while maintaining good mechanical properties.
A silicone rubber composition of a specific composition, including high molecular weight organopolysiloxane, reinforced silica and sodium polyacrylate, is used to form silicone rubber with a high sliding property that reduces the coefficient of friction when wet with high sliding properties.
The silicone rubber surface has a significantly reduced friction coefficient when wet, and the friction coefficient is restored during drying, and maintains good mechanical properties.
Smart Images

Figure 0007628940000001 
Figure 0007628940000002 
Figure 0007628940000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a millable silicone rubber composition, a method for producing the same, and a cured product thereof. [Background technology]
[0002] Silicone rubber has excellent weather resistance, electrical properties, low compression set, heat resistance, cold resistance, etc., and is therefore widely used in various fields, including electrical equipment, automobiles, construction, medicine, and food. For example, it is used in rubber contacts used as rubber contacts in remote controllers, typewriters, word processors, computer terminals, musical instruments, etc.; construction gaskets; various rolls such as copier rolls, developing rolls, transfer rolls, charging rolls, and paper feed rolls; anti-vibration rubbers for audio equipment, etc.; and packing for compact disks used in computers. Currently, the demand for silicone rubber is increasing, and the development of silicone rubber with excellent properties is desired.
[0003] Silicone rubber usually has a high coefficient of friction and is used in various products as a member for preventing slippage. On the other hand, there is also a high demand for silicone rubber with good surface slipperiness. A method of adding a low-compatible oil is known as a method for lowering the surface friction coefficient of silicone rubber. For example, when the silicone rubber is dimethyl silicone, by adding a low-viscosity oil with an introduced phenyl group, the phenyl oil with low compatibility bleeds out from within the molded product to the surface after molding, lowering the surface friction coefficient. These materials are widely used in oil-bleed materials for automobiles, etc. (Patent Document 1, Patent Document 2).
[0004] However, these oil-bleeding materials have the problem that the oil component bleeds out onto the surface, and this oil may transfer to other materials and cause stains. As a method for providing slipperiness without adding phenyl oil, there is a method of adding a polymer that does not contain an alkenyl group (Patent Document 3), but further improvements have been desired.
[0005] A composition containing a two-liquid addition-curing silicone composition and a sodium polyacrylate-based superabsorbent polymer is exemplified as an adhesive for wet tissues (Patent Document 4), but since this is an adhesive, there is no description regarding its slipperiness.
[0006] There is a description of an elastomer composition in which a hydrophilic polymer such as sodium polyacrylate and an inorganic salt are added to a base elastomer (Patent Document 5). After vulcanizing the elastomer composition, the inorganic salt reacts with the water absorbed via the hydrophilic polymer and crystallizes by contacting it with water for 2 to 6 hours. It is described that this results in high tensile strength and high hardness, but there is no description of slipperiness, and no examples of silicone rubber. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2006 / 070947 [Patent Document 2] JP 2009-185254 A [Patent Document 3] JP 2008-195939 A [Patent Document 4] Special Publication No. 2018-510675 [Patent Document 5] JP 2017-222848 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a silicone rubber composition that becomes a silicone rubber (cured product) that exhibits excellent slipperiness when wetted with water and loses that slipperiness when dried. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides (A) an organopolysiloxane having two or more alkenyl groups in one molecule and an average degree of polymerization of 100 or more, represented by the following average composition formula (1): R 1 a SiO (4-a) / 2 (1) (In the formula, R 1 are independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and a is a positive number of 1.95 to 2.05. (B) The specific surface area by the BET method is 50 m 2 / g or more of reinforcing silica; 10 to 100 parts by mass, (C) sodium polyacrylate; 0.3 to 15 parts by mass per 100 parts by mass of the total of the (A) component and the (B) component, (D) a hardener; an effective amount The present invention provides a silicone rubber composition comprising:
[0010] Such a silicone rubber composition can provide a silicone rubber (cured product) that exhibits excellent slipperiness when wetted with water, and loses this slipperiness when dried.
[0011] The molecular weight of the component (C) is preferably 10,000 to 7,000,000.
[0012] Such a silicone rubber composition exhibits a sufficiently low dynamic friction coefficient, exhibits high slip properties, and does not deteriorate the physical properties of the cured product.
[0013] The silicone rubber composition is preferably an organic peroxide curable silicone rubber composition.
[0014] The silicone rubber composition of the present invention can be of such a curing type.
[0015] The silicone rubber composition is preferably an addition reaction curable silicone rubber composition.
[0016] The silicone rubber composition of the present invention can be of such a curing type.
[0017] The present invention also provides a method for producing the above silicone rubber composition, comprising the steps of: A step of mixing the component (C) with a part of the component (A) to obtain a sodium polyacrylate paste; mixing the sodium polyacrylate paste with the remaining components (A), (B) and (D) to obtain the silicone rubber composition; The present invention provides a method for producing a silicone rubber composition comprising the steps of:
[0018] Such a method for producing a silicone rubber composition makes it easier to mix component (C) with the other components. Effect of the Invention
[0019] According to the present invention, it is possible to provide a silicone rubber composition (millable type silicone rubber composition) that can provide a silicone rubber with an effectively reduced surface friction coefficient by wetting the cured product (molded product) with water, as well as a method for producing the same and the cured product thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] As described above, there has been a demand for a silicone rubber composition that develops excellent slipperiness when wetted with water and that turns into a silicone rubber (cured product) that loses this slipperiness when dried.
[0021] As a result of extensive research to achieve the above object, the present inventors have discovered that adding a specific amount of sodium polyacrylate to a heat-curable silicone rubber composition results in a silicone rubber composition that has sufficiently excellent slip properties when the surface of the cured product is wetted with water.
[0022] That is, the present invention provides: (A) an organopolysiloxane having two or more alkenyl groups in one molecule and an average degree of polymerization of 100 or more, represented by the following average composition formula (1): R 1 a SiO (4-a) / 2 (1) (In the formula, R 1 are independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and a is a positive number of 1.95 to 2.05. (B) The specific surface area by the BET method is 50 m 2 / g or more of reinforcing silica; 10 to 100 parts by mass, (C) sodium polyacrylate; 0.3 to 15 parts by mass per 100 parts by mass of the total of the (A) component and the (B) component, (D) a hardener; an effective amount The silicone rubber composition comprises:
[0023] The present invention will now be described in more detail. In this specification, the specific surface area is a value measured by the BET method. The millable composition generally means a composition that is high-viscosity and non-liquid and does not have self-fluidity at room temperature (25°C), and can be uniformly kneaded under shear stress with a kneader such as a roll mill (e.g., two-roll or three-roll). The organopolysiloxane raw rubber generally means a non-liquid organopolysiloxane component that has a high degree of polymerization (high viscosity) and does not have self-fluidity at room temperature (25°C).
[0024] [Silicone rubber composition] [(A) Organopolysiloxane] In the present invention, component (A) is an organopolysiloxane represented by the following average composition formula (1), which has two or more alkenyl groups in one molecule and has an average degree of polymerization of 100 or more. R 1 a SiO (4-a) / 2 (1) (In the formula, R 1 are independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and a is a positive number of 1.95 to 2.05.
[0025] In the above average composition formula (1), R 1are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, and specifically include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and octyl groups, cycloalkyl groups such as cyclopentyl and cyclohexyl groups, alkenyl groups such as vinyl, allyl, propenyl, butenyl, and hexenyl groups, cycloalkenyl groups such as cyclohexenyl groups, aryl groups such as phenyl and tolyl groups, aralkyl groups such as benzyl and 2-phenylethyl groups, and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms such as fluorine and chlorine, such as chloromethyl and trifluoropropyl groups. Among the above, methyl, vinyl, phenyl, and trifluoropropyl groups are preferred, and methyl and vinyl groups are particularly preferred.
[0026] In particular, the organopolysiloxane as component (A) is characterized by having two or more alkenyl groups in one molecule, preferably 2 to 50 alkenyl groups, and particularly preferably 2 to 20 alkenyl groups. The alkenyl group may be a cyclic aliphatic unsaturated group such as a cycloalkenyl group. The alkenyl group is preferably a vinyl group or an allyl group, and particularly preferably a vinyl group.
[0027] Also, all R 1 Of these, 0.01 to 20 mol %, and particularly 0.02 to 10 mol %, are preferably alkenyl groups. The alkenyl groups may be bonded to silicon atoms at the molecular chain terminals, or to silicon atoms in the middle of the molecular chain (non-terminal), or both, but it is preferred that at least one of them is bonded to a silicon atom at a molecular chain terminal.
[0028] Also, all R 1 Of these, 80 mol % or more, preferably 90 mol % or more, more preferably 95 mol % or more, and further preferably all R excluding alkenyl groups. 1 It is preferred that is an alkyl group, particularly a methyl group.
[0029] The letter a is a positive number of 1.95 to 2.05, preferably 1.98 to 2.02, and more preferably 1.99 to 2.01.
[0030] The molecular structure of the organopolysiloxane, which is the component (A), is preferably linear or partially branched. Specifically, the diorganosiloxane unit (R 1 2 SiO 2 / 2 , R 1 is the same as above, hereinafter the same) is preferably composed of only repetitions of dimethylsiloxane units, or is preferably composed of diorganosiloxane units such as diphenylsiloxane units having phenyl groups, vinyl groups, 3,3,3-trifluoropropyl groups, or the like as substituents, methylphenylsiloxane units, methylvinylsiloxane units, or methyl-3,3,3-trifluoropropylsiloxane units, introduced as part of the dimethylpolysiloxane structure composed of repetitions of dimethylsiloxane units that constitute the main chain.
[0031] Both ends of the molecular chain may be, for example, a triorganosiloxy group (R 1 3 SiO 1 / 2 ) or the like.
[0032] Such organopolysiloxanes can be obtained, for example, by cohydrolytic condensation or hydrolytic condensation of one or more organohalogenosilanes, or by ring-opening polymerization of a cyclic polysiloxane (e.g., a siloxane trimer or tetramer) using an alkaline or acidic catalyst.
[0033] The average degree of polymerization of the organopolysiloxane is 100 or more (usually 100 to 100,000), preferably 1,000 to 100,000, more preferably 2,000 to 50,000, and particularly preferably 3,000 to 20,000. It is preferable that the organopolysiloxane has no self-flowability at room temperature (25°C), and is in a so-called raw rubber state (non-liquid state). If the average degree of polymerization is less than 100, problems such as roll adhesion will occur when the compound is made, and roll workability will deteriorate. The average degree of polymerization is determined as the average degree of polymerization from the weight average molecular weight in terms of polystyrene by gel permeation chromatography (GPC) analysis measured under the following conditions. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (THF solution with a concentration of 0.5% by mass)
[0034] The component (A) may be a single type, or a mixture of two or more types differing in molecular weight, degree of polymerization, or molecular structure.
[0035] [(B) Reinforcing Silica] The reinforcing silica of component (B) acts as a component that imparts excellent mechanical properties to the resulting silicone rubber composition. The reinforcing silica may be precipitated silica (wet silica) or fumed silica (dry silica), and has a large number of silanol groups (SiOH) on its surface. In the present invention, the specific surface area of the reinforcing silica of component (B) measured by the BET method is 50 m 2 / g or more, and preferably 100 to 400m 2 / g. This specific surface area is 50m 2 If it is less than 1 / g, the reinforcing effect of component (B) will be insufficient.
[0036] The reinforcing silica of component (B) may be used in an untreated state, or may be surface-treated, as necessary, with an organosilicon compound such as organopolysiloxane, organopolysilazane, chlorosilane, alkoxysilane, etc. These reinforcing silicas may be used alone or in combination of two or more.
[0037] The amount of reinforcing silica (B) blended is 10 to 100 parts by mass, preferably 10 to 80 parts by mass, and more preferably 20 to 70 parts by mass, per 100 parts by mass of the organopolysiloxane (A). If the amount of component (B) is less than 10 parts by mass per 100 parts by mass of the organopolysiloxane (A), the mechanical properties such as tensile strength and tear strength of the silicone rubber cured product obtained by curing the silicone rubber composition will be insufficient, while if the amount of component (B) exceeds 100 parts by mass, the processability of the obtained silicone rubber composition will decrease.
[0038] [(C) Sodium polyacrylate] The sodium polyacrylate of the component (C) absorbs water and expands when it comes into contact with water. It then seeps out onto the surface of the silicone rubber cured product, and exhibits slipperiness. A molecular weight of 10,000 to 7,000,000 is preferable because the slipperiness of the silicone rubber cured product when wetted with water is good, and 100,000 to 7,000,000 is more preferable, and 1,000,000 to 6,600,000 is even more preferable. A molecular weight of 10,000 or more sufficiently reduces the dynamic friction coefficient, and exhibits high slipperiness. If it is 7,000,000 or less, the physical properties of the cured product are not deteriorated. When the molecular weight of the sodium polyacrylate used has a distribution, it is preferable that both the upper and lower limits are within the above ranges.
[0039] The amount of component (C) added is 0.3 to 15 parts by mass, preferably 0.3 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the total of components (A) and (B). If the amount is less than 0.3 parts by mass, good slip properties cannot be obtained, and if it exceeds 15 parts by mass, the physical properties of the cured product may deteriorate.
[0040] [(D) Hardener] The curing agent for component (D) is not particularly limited as long as it can cure the silicone rubber composition, but the following (D-1) organic peroxide curing agent and / or (D-2) addition reaction curing agent can be used.
[0041] (D-1) Organic peroxide curing agent Examples of (D-1) organic peroxide curing agents include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, p-methylbenzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, and 1,6-hexanediol-bis-t-butylperoxycarbonate.
[0042] By adding an organic peroxide curing agent to a silicone rubber compound, which is a composition containing components (A), (B), and (C), an organic peroxide curing type silicone rubber composition can be obtained. The amount of organic peroxide curing agent added is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, per 100 parts by mass of component (A). If the amount is 0.1 part by mass or more, curing will not be insufficient, and if it is 10 parts by mass or less, the silicone rubber cured product will not yellow due to decomposition residues of the organic peroxide curing agent.
[0043] (D-2) Addition reaction curing agent As the addition reaction curing agent (D-2), a combination of an organohydrogenpolysiloxane and a hydrosilylation catalyst can be used. By adding the addition reaction curing agent to a silicone rubber compound, an addition reaction curing type silicone rubber composition can be obtained.
[0044] The organohydrogenpolysiloxane may have a linear, cyclic, branched, or three-dimensional network structure, so long as it contains preferably 2 or more, more preferably 3 to 200, and even more preferably about 4 to 100 hydrogen atoms bonded to silicon atoms in one molecule (i.e., hydrosilyl groups). Any organohydrogenpolysiloxane known as a curing agent for addition reaction curing silicone rubber compositions can be used, and for example, an organohydrogenpolysiloxane represented by the following average composition formula (2) can be used. R 2 r H s SiO (4-r-s) / 2 (2)
[0045] In the above average composition formula (2), R 2 R independently represents a monovalent hydrocarbon group, preferably excluding an aliphatic unsaturated bond. 2 The monovalent hydrocarbon group preferably has 1 to 12 carbon atoms, more preferably 1 to 8 carbon atoms. 2 Specific examples of the alkyl group include alkyl groups such as a methyl group, an ethyl group, and a propyl group; cycloalkyl groups such as a cyclohexyl group; aryl groups such as a phenyl group and a tolyl group; aralkyl groups such as a benzyl group, a 2-phenylethyl group, and a 2-phenylpropyl group; and groups in which some or all of the hydrogen atoms of these groups have been substituted with halogen atoms or the like, for example, a 3,3,3-trifluoropropyl group.
[0046] Incidentally, r preferably satisfies 0 < r < 3, more preferably 0.5 ≤ r ≤ 2.2, and even more preferably 1.0 ≤ r ≤ 2.0. Also, s preferably satisfies 0 < s ≤ 3, more preferably 0.002 ≤ s ≤ 1.1, and even more preferably 0.005 ≤ s ≤ 1. Further, it is a positive number satisfying 0 < r + s ≤ 3, more preferably 1 ≤ r + s ≤ 3, and even more preferably 1.002 ≤ r + s ≤ 2.7.
[0047] The organohydrogenpolysiloxane preferably has 2 or more, more preferably 3 or more hydrosilyl groups in one molecule, and these may be at the molecular chain ends, in the middle of the molecular chain, or both. Also, as this organohydrogenpolysiloxane, the viscosity at 25°C is preferably 0.5 to 10,000 mPa·s, particularly 1 to 300 mPa·s. In the present invention, the viscosity is a value measured by a rotational viscometer at 25°C as described in JIS K7117-1:1999.
[0048] Specific examples of such organohydrogenpolysiloxanes include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both ends, dimethylsiloxane-methylhydrogensiloxane copolymer capped with trimethylsiloxy groups at both ends, dimethylpolysiloxane capped with dimethylhydrogensiloxy groups at both ends, dimethylhydrogensiloxane-methylhydrogensiloxane copolymer capped with dimethylhydrogensiloxy groups at both ends, dimethylpolysiloxane capped with dimethylhydrogensiloxy groups at both ends, dimethylhydrogensiloxy poly ... end-blocked dimethylsiloxane-methylhydrogensiloxane copolymer, end-blocked methylhydrogensiloxane-diphenylsiloxane copolymer with trimethylsiloxy groups at both ends, end-blocked methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane copolymer with trimethylsiloxy groups at both ends, end-blocked methylhydrogensiloxane-methylphenylsiloxane-dimethylsiloxane copolymer, end-blocked methylhydrogensiloxane-dimethylsiloxane copolymer with dimethylhydrogensiloxy groups at both ends, end-blocked methylhydrogensiloxane-dimethylsiloxane-diphenylsiloxane copolymer with dimethylhydrogensiloxy groups at both ends, (CH 3 ) 2 HSiO 1 / 2 Units and (CH 3 ) 3 SiO 1 / 2 Units and SiO 4 / 2 A copolymer consisting of (CH 3 ) 2 HSiO 1 / 2 Units and SiO 4 / 2 A copolymer consisting of (CH 3 ) 2 HSiO 1 / 2 Units and SiO 4 / 2 Units and (C 6 H 5 ) 3 SiO 1 / 2and copolymers consisting of these units, and compounds in which part or all of the methyl groups in the above exemplary compounds have been substituted with other alkyl groups, phenyl groups, or the like.
[0049] The amount of the organohydrogenpolysiloxane is preferably 0.1 to 40 parts by mass per 100 parts by mass of the total amount of the silicone rubber compound (containing components (A), (B), and (C)). The ratio of hydrogen atoms bonded to silicon atoms (hydrosilyl groups) per alkenyl group in component (A) is preferably in the range of 0.5 to 10, more preferably 0.7 to 5. If the ratio is 0.5 or more, crosslinking is sufficient and sufficient mechanical strength is obtained, while if the ratio is 10 or less, the physical properties after curing are not reduced, and in particular, the heat resistance is not deteriorated and the compression set is not increased.
[0050] The hydrosilylation catalyst is a catalyst that causes a hydrosilylation addition reaction between the alkenyl group of the component (A) and the silicon-bonded hydrogen atom (hydrosilyl group) of the organohydrogenpolysiloxane. Examples of the hydrosilylation catalyst include platinum group metal catalysts, including simple platinum group metals and their compounds, and those that have been known as catalysts for addition reaction curing silicone rubber compositions can be used. For example, platinum catalysts such as particulate platinum metal adsorbed on a carrier such as silica, alumina, or silica gel, platinic chloride, chloroplatinic acid, and alcohol solutions of chloroplatinic acid hexahydrate, palladium catalysts, and rhodium catalysts can be mentioned, with platinum or platinum compounds (platinum catalysts) being preferred.
[0051] The amount of hydrosilylation catalyst added may be any amount sufficient to promote the addition reaction, and is usually used in the range of 1 ppm by mass to 1% by mass, calculated as the amount of platinum group metal, relative to component (A), with the range of 5 to 500 ppm by mass being preferred. If the amount added is 1 ppm by mass or more, the addition reaction is sufficiently promoted and curing is sufficient, while if it is 1% by mass or less, sufficient reactivity is maintained and it is not uneconomical.
[0052] In addition to the hydrosilylation catalyst, an addition reaction inhibitor may be used according to the purpose of the present invention in order to adjust the curing rate. Specific examples of such an inhibitor include acetylene alcohol inhibitors such as ethynylcyclohexanol, and organosilicon compound inhibitors such as 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, and bis[(1,1-dimethyl-2-propyn-1-yl)oxy]dimethylsilane. The addition reaction inhibitor may be used alone or in combination of two or more.
[0053] In addition, the silicone rubber compound can also be blended with the (D-1) and (D-2) components in the above-mentioned ranges of blending amounts to produce a co-vulcanization type silicone rubber composition (millable type silicone rubber composition) that combines addition reaction curing and organic peroxide curing.
[0054] [Other ingredients] In addition to the above-mentioned components, the silicone rubber composition of the present invention (millable type silicone rubber composition) can contain, as necessary, fillers such as crushed quartz, crystalline silica, diatomaceous earth, calcium carbonate, etc., colorants, tear strength improvers, acid acceptors, thermal conductivity improvers such as alumina, boron nitride, etc., release agents, and filler dispersants such as various alkoxysilanes, in particular phenyl group-containing alkoxysilanes and their hydrolysates, diphenylsilanediol, carbon functional silane, dimethylpolysiloxane having silanol groups at both ends, and 3,3,3-trifluoropropylmethylpolysiloxane having silanol groups at both ends, as well as other fillers and additives known in the art for use in thermosetting silicone rubber compositions.
[0055] [Method of manufacturing silicone rubber composition] The silicone rubber composition of the present invention can be produced by mixing a composition containing 100 parts by mass of component (A) and 10 to 100 parts by mass of component (B), heat treating the mixture to obtain a base compound, and then adding an effective amount of component (D) within the above-mentioned blending amount range to 100 parts by mass of the silicone rubber compound obtained by adding 0.3 to 15 parts by mass of component (C) per 100 parts by mass of the base compound.
[0056] It should be noted that the method for obtaining the silicone rubber composition of the present invention is not limited to the above. For example, there are cases where no heat treatment is carried out when the (A) component and the (B) component are mixed to obtain the base compound, and cases where, instead of adding the (C) component to the obtained base compound, the (C) component is mixed together with the (A) and (B) components when compounding the base compound.
[0057] Furthermore, in the method for producing the silicone rubber composition, instead of adding component (C) alone, a sodium polyacrylate paste is prepared by mixing component (C) with a part of component (A), and the sodium polyacrylate paste is added to the base compound so that the blending amount of component (C) falls within the above-mentioned range to prepare a silicone rubber compound, and further an effective amount of component (D) within the above-mentioned blending amount range can be added to produce the silicone rubber composition.
[0058] <Curing conditions> The silicone rubber composition of the present invention can be cured under known curing conditions by a known curing method to obtain a cured product. Specifically, the composition can be cured by heating at preferably 25 to 200°C, more preferably 80 to 160°C. The heating time is preferably 0.5 minutes to 5 hours, more preferably 1 minute to 3 hours. Furthermore, by performing secondary vulcanization at 150 to 250°C for 1 to 10 hours, removal of decomposition residues of the organic peroxide curing agent and stabilization of physical properties can be expected.
[0059] The silicone rubber cured product obtained by curing the silicone rubber composition of the present invention has excellent slip properties when the sheet surface is wetted with water. EXAMPLES
[0060] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0061] Physical property measurement method [Measurement method] In the present examples and comparative examples, the prepared cured products (test sheets) were evaluated as follows.
[0062] [Various physical properties] The resulting silicone rubber cured product was measured for various physical properties (hardness (Durometer A hardness tester), tensile strength, and elongation at break) in accordance with JIS K 6249:2003.
[0063] [Kinematic friction coefficient] The dynamic friction coefficient of the test sheet was measured using an automatic friction and wear analyzer TSf-503 (Kyowa Interface Science Co., Ltd.) under conditions of a load of 1 kg, a tensile speed of 10 mm / s, and a point contact (steel ball), when the same spot was slid 10 times (initial). The dynamic friction coefficient was also measured when a drop of water was dropped on the dynamic friction coefficient measurement location (water drop), and then the water was dried at room temperature (25°C) for 48 hours, and the dynamic friction coefficient was measured (dry). Note that since the initial dynamic friction coefficients of Example 8 and Comparative Example 5 were too large compared to the other Examples, the load was changed from 1 kg to 500 g for measurement.
[0064] [Touch test] The slipperiness was evaluated when the test sheet was rubbed with a finger moistened with water. ◎: Slippery (slippery) 〇: Smooth (not slippery) ×: Non-slip
[0065] [Preparation of sodium polyacrylate paste] 100 parts by mass of organopolysiloxane gum composed of 99.850 mol% dimethylsiloxane units, 0.125 mol% methylvinylsiloxane units, and 0.025 mol% dimethylvinylsiloxane units and having an average degree of polymerization of approximately 8,000 and 100 parts by mass of sodium polyacrylate (1) (manufactured by Wako Pure Chemical Industries, Ltd., degree of polymerization: 22,000 to 70,000 (molecular weight: 2,069,000 to 6,583,000)) were kneaded using a two-roll mill and then a three-roll mill to prepare a sodium polyacrylate paste.
[0066] [Example 1] As component (A), 100 parts by mass of organopolysiloxane raw rubber consisting of 99.850 mol % dimethylsiloxane units, 0.125 mol % methylvinylsiloxane units, and 0.025 mol % dimethylvinylsiloxane units and having an average degree of polymerization of about 8,000, and as component (B), fumed silica (trade name: Aerosil 200, manufactured by Nippon Aerosil Co., Ltd., specific surface area by BET method: 200 m) were used. 2 After adding 40 parts by mass of dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity of 15 mPa s at 25°C, the mixture was mixed in a kneader and heat-treated at 170°C for 2 hours to prepare base compound (1).
[0067] 0.5 parts by mass of sodium polyacrylate (1) (manufactured by Wako Pure Chemical Industries, Ltd., polymerization degree: 22,000 to 70,000 (molecular weight: 2,069,000 to 6,583,000)) was added to 100 parts by mass of the base compound (1) to prepare a silicone rubber compound (1). 0.4 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane as a curing agent was mixed with 100 parts by mass of the silicone rubber compound (1) to prepare a silicone rubber composition. The silicone rubber composition was then heated at 165°C and 70 kgf / cm. 2 A test sheet (1) was prepared by press curing for 10 minutes under the above conditions and then post curing for 4 hours at 200° C., and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0068] [Example 2] A test sheet (2) was prepared in the same manner as in Example 1, except that the amount of sodium polyacrylate (1) was 5.0 parts by mass, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0069] [Example 3] A test sheet (3) was prepared in the same manner as in Example 1, except that sodium polyacrylate (1) was replaced with sodium polyacrylate (2) (product name: AQUALIC FH-S, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,000,000 to 5,000,000), and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0070] [Example 4] A test sheet (4) was prepared in the same manner as in Example 1, except that sodium polyacrylate (1) was replaced with sodium polyacrylate (3) (product name: AQUALIC DL-100, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,500), and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0071] [Example 5] A test sheet (5) was prepared in the same manner as in Example 1, except that the sodium polyacrylate paste prepared above was used as 1 part by mass instead of the sodium polyacrylate (1), and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0072] [Example 6] As component (A), 100 parts by mass of organopolysiloxane raw rubber consisting of 99.850 mol % dimethylsiloxane units, 0.125 mol % methylvinylsiloxane units, and 0.025 mol % dimethylvinylsiloxane units and having an average degree of polymerization of about 8,000, and as component (B), fumed silica (trade name: Aerosil 200, manufactured by Nippon Aerosil Co., Ltd., specific surface area by BET method: 200 m) were used. 2 After adding 60 parts by mass of dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity of 15 mPa s at 25°C, the mixture was mixed in a kneader and heat-treated at 170°C for 2 hours to prepare base compound (2).
[0073] 0.5 parts by mass of sodium polyacrylate (2) (trade name: AQUALIC FH-S, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,000,000 to 5,000,000) was added to 100 parts by mass of the base compound (2) to prepare a silicone rubber compound (2). 0.9 parts by mass of methylhydrogenpolysiloxane (degree of polymerization: 38, hydrosilyl group: 0.00725 mol / g) having a hydrosilyl group on the side chain as a curing agent, 0.04 parts by mass of ethynylcyclohexanol as an addition reaction inhibitor, and 0.05 parts by mass of a platinum catalyst (Pt concentration: 1% by mass) were mixed with 100 parts by mass of the silicone rubber compound (2) to prepare a silicone rubber composition. The silicone rubber composition was then heated at 120°C and 70 kgf / cm. 2 A test sheet (6) was prepared by press curing for 10 minutes under the above conditions and then post curing for 4 hours at 200° C., and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0074] [Example 7] As component (A), 100 parts by mass of organopolysiloxane gum composed of 99.850 mol % dimethylsiloxane units, 0.125 mol % methylvinylsiloxane units, and 0.025 mol % dimethylvinylsiloxane units and having an average degree of polymerization of about 8,000, and as component (B), fumed silica (trade name: Aerosil R972, manufactured by Nippon Aerosil Co., Ltd., specific surface area measured by BET method: 110 m 2 After adding 20 parts by mass of 100 parts by mass of 1 / g of ethyl acetate, the mixture was mixed in a kneader to prepare a base compound (3).
[0075] 0.5 parts by mass of sodium polyacrylate (2) (product name: AQUALIC FH-S, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,000,000 to 5,000,000) was added to 100 parts by mass of the base compound (3) to prepare a silicone rubber compound (3). 0.4 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane as a curing agent was mixed with 100 parts by mass of the silicone rubber compound (3) to prepare a silicone rubber composition. The silicone rubber composition was then heated at 165°C and 70 kgf / cm. 2A test sheet (7) was prepared by press curing for 10 minutes under the above conditions and then post curing for 4 hours at 200° C., and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0076] [Example 8] As component (A), 100 parts by mass of organopolysiloxane gum composed of 99.825 mol % of 3,3,3-trifluoropropylmethylsiloxane units, 0.125 mol % of methylvinylsiloxane units, and 0.05 mol % of dimethylvinylsiloxane units and having an average degree of polymerization of about 4,000, and as component (B), fumed silica (trade name: Aerosil 200, manufactured by Nippon Aerosil Co., Ltd., specific surface area by BET method: 200 m) were used. 2 After adding 40 parts by mass of 1,2,3-trifluoropropylmethylsiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity of 15 mPa s at 25°C, and 5 parts by mass of diphenylsilanediol, the mixture was mixed in a kneader and heat-treated at 150°C for 2 hours to prepare base compound (4).
[0077] 0.5 parts by mass of sodium polyacrylate (2) (product name: AQUALIC FH-S, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,000,000 to 5,000,000) was added to 100 parts by mass of the base compound (4) to prepare a silicone rubber compound (4). 0.6 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane as a curing agent was mixed with 100 parts by mass of the silicone rubber compound (4) to prepare a silicone rubber composition. The silicone rubber composition was then heated at 165°C and 70 kgf / cm. 2 A test sheet (8) was prepared by press curing for 10 minutes under the above conditions and then post curing for 4 hours at 200° C., and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0078] [Example 9] As component (A), 100 parts by mass of organopolysiloxane raw rubber consisting of 99.850 mol % dimethylsiloxane units, 0.125 mol % methylvinylsiloxane units, and 0.025 mol % dimethylvinylsiloxane units and having an average degree of polymerization of about 8,000, and as component (B), fumed silica (trade name: Aerosil 200, manufactured by Nippon Aerosil Co., Ltd., specific surface area by BET method: 200 m) were used. 2 Then, 40 parts by mass of dimethylpolysiloxane having silanol groups at both ends, an average degree of polymerization of 4, and a viscosity at 25°C of 15 mPa s, and 0.52 parts by mass of sodium polyacrylate (2) (product name: AQUALIC FH-S, manufactured by Nippon Shokubai Co., Ltd., molecular weight: 3,000,000 to 5,000,000) as component (C) were added, and the mixture was mixed in a kneader and heat-treated at 170°C for 2 hours to prepare a base compound (5) (silicone rubber compound (5)).
[0079] 100 parts by mass of the base compound (5) was mixed with 0.4 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane as a curing agent to prepare a silicone rubber composition. The composition was then subjected to a test at 165°C and 70 kgf / cm 2 A test sheet (9) was prepared by press curing for 10 minutes under the above conditions and then post curing for 4 hours at 200° C., and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0080] [Comparative Example 1] A test sheet (10) was prepared in the same manner as in Example 1, except that sodium polyacrylate (1) was not added, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0081] [Comparative Example 2] A test sheet (11) was prepared in the same manner as in Example 1, except that the amount of sodium polyacrylate (1) was 0.1 parts by mass, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0082] [Comparative Example 3] A test sheet (12) was prepared in the same manner as in Example 6, except that sodium polyacrylate (2) was not added, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0083] [Comparative Example 4] A test sheet (13) was prepared in the same manner as in Example 7, except that sodium polyacrylate (2) was not added, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0084] [Comparative Example 5] A test sheet (14) was prepared in the same manner as in Example 8, except that sodium polyacrylate (2) was not added, and various physical properties, dynamic friction coefficient, and slipperiness were measured.
[0085] The results are shown in Tables 1 to 5. The units of values in the tables are parts by mass.
[0086] [Table 1]
[0087] [Table 2]
[0088] [Table 3]
[0089] [Table 4]
[0090] [Table 5]
[0091] <Evaluation Results> Regarding the dynamic friction coefficient when water was dropped onto the test sheet made from the silicone rubber composition of the present invention, the dynamic friction coefficient when water was dropped onto the test sheet of the Example tended to be significantly lower than that of the Comparative Example measured under the same conditions. In addition, the results of the finger touch test showed that all of the Examples were rated as ◎ or ◯, whereas all of the Comparative Examples were rated as ×, confirming that the test sheet using the present invention exhibits slipperiness when wetted with water.
[0092] In addition, when water was dropped onto the test sheets of the examples and then the sheets were dried for 48 hours, the dynamic friction coefficients were all approximately the same as the initial values. This confirmed that, in the test sheets using the present invention, the slipperiness exhibited by wetting with water disappears when the sheets are dried.
[0093] The hardness, tensile strength, and elongation at break of the test sheets produced in the examples and comparative examples were comparable when measured under the same conditions.
[0094] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. (A) 100 parts by mass of an organopolysiloxane represented by the following average composition formula (1) having two or more alkenyl groups in one molecule and an average degree of polymerization of 100 or more: R 1 a SiO (4-a)/2 (1) (In the formula, R 1 are independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and a is a positive number from 1.95 to 2.
05. (B) A material with a specific surface area of 50 m2 measured by the BET method 2 / g or more of reinforcing silica; 10 to 100 parts by mass, (C) sodium polyacrylate; 0.3 to 5 parts by mass per 100 parts by mass of the total of the (A) component and the (B) component, (D) a curing agent; an effective amount A silicone rubber composition comprising:
2. 2. The silicone rubber composition according to claim 1, wherein the molecular weight of component (C) is 10,000 to 7,000,000.
3. 3. The silicone rubber composition according to claim 1, which is an organic peroxide curable silicone rubber composition.
4. 3. The silicone rubber composition according to claim 1, which is an addition reaction curing type silicone rubber composition.
5. A method for producing the silicone rubber composition according to any one of claims 1 to 4, comprising the steps of: A step of mixing the component (C) with a part of the component (A) to obtain a sodium polyacrylate paste; mixing the sodium polyacrylate paste with the remaining components (A), (B) and (D) to obtain the silicone rubber composition; 2. A method for producing a silicone rubber composition comprising the steps of:
Citation Information
Patent Citations
Water-absorbing silicone rubber composition
JP1986236856A
Friction reducing mixed composition
JP1997188780A
Water-swelling silicone rubber composition
JP1999140316A
Addition crosslinkable silicone material having low coefficient of friction
JP2008195939A
Oil-bleeding property-added curable silicone rubber composition and cured article of the same
JP2009185254A